2018
DOI: 10.1016/j.jamcollsurg.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Imaging Features and Postoperative Hepatic Insufficiency: A Multi-Institutional Expanded Cohort

Abstract: Quantitative imaging features are independently associated with PHLI and are a promising preoperative risk stratification tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Strict patient selection and precise assessment of the size and quality of the remnant liver are pivotal to the decision-making process[ 14 ]. Although experiences gained from previous studies have indicated that after extended hepatectomy involving 70% to 75% of the liver, the remnant liver can still function well in non-cirrhosis patients[ 15 , 16 ], the strategy may need to be adjusted in the application of ERLA. A major feature of endoscopic retrograde appendicitis treatment (ERAT) is the longer CIT compared with ordinary liver transplantation (LT)[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strict patient selection and precise assessment of the size and quality of the remnant liver are pivotal to the decision-making process[ 14 ]. Although experiences gained from previous studies have indicated that after extended hepatectomy involving 70% to 75% of the liver, the remnant liver can still function well in non-cirrhosis patients[ 15 , 16 ], the strategy may need to be adjusted in the application of ERLA. A major feature of endoscopic retrograde appendicitis treatment (ERAT) is the longer CIT compared with ordinary liver transplantation (LT)[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strict patient selection and precise assessment of the size and quality of the remnant liver are pivotal to the decision-making process (14). Although experiences gained from previous studies have indicated that after extended hepatectomy involving 70 to 75% of the liver, the remnant liver can still function well in non-cirrhosis patients (15,16), the strategy may need to be adjusted in the application of ERLA according to the speci c situation. A major feature of ERAT is the longer CIT compared with ordinary LT (17).…”
Section: Discussionmentioning
confidence: 99%
“…Strict patient selection and precise assessment of the size and quality of the remnant liver are pivotal to the decision-making process (14). Although experiences gained from previous studies have indicated that after extended hepatectomy involving 70 to 75% of the liver, the remnant liver can still function well in non-cirrhosis patients (15,16), the strategy may need to be adjusted in the application of ERLA. A major feature of ERAT is the longer CIT compared with ordinary LT (17).…”
Section: Discussionmentioning
confidence: 99%